Transformaciones económicas y sociales en el departamento de Cachi (Salta) a fines del siglo XIX - Lera, Mariana Ester (Centro de Historia Argentina y Americana, 2006)
The aim of this piece of work is to study the economic and social changes produced in the town of Cachi, department of the province of Salta, Argentina, towards the end of the 19 ° century. To this end, the town's agricultural structure is researched, laying emphasis on d land possession, man power, production and market. Even thought it's a local history matter, an analysis about regional history is added to it also; which allows to determine how the town joins the regional space formed at the end of the changes and the continuity in the production, the possession of land, the appearance of new forms of land production and the agricultural workers' situation are studied.